The sparing effect of ultra-high dose rate irradiation on the esophagus - Ren, Wenting; Hou, Lu; Zhang, Ke; Chen, Huan; Feng, Xin; Jiang, Ziming; Shao, Fei; Dai, Jianrong; Gao, Yibo; He, Jie (Frontiers in Oncology, 2024)
Background and purpose Current studies have substantiated the sparing effect of ultra-high dose rate irradiation (FLASH) in various organs including the brain, lungs, and intestines. Whether this sparing effect extends to esophageal tissue remains unexplored. This study aims to compare the different responses of esophageal tissue in histological and protein expression levels following conventional dose rate irradiation (CONV) and FLASH irradiation to ascertain the presence of a sparing effect. Methods and materials C57 female mice were randomly divided into three groups: control, CONV, and FLASH groups. The chest region of the mice in the radiation groups was exposed to a prescribed dose of 20 Gy using a modified electron linear accelerator. The CONV group received an average dose rate of 0.1 Gy/s, while the FLASH group received an average dose rate of 125 Gy/s. On the 10th day after irradiation, the mice were euthanized and their esophagi were collected for histopathological analysis. Subsequently, label-free proteomic quantification analysis was performed on esophageal tissue. The validation process involved analyzing transmission electron microscopy images and utilizing the parallel reaction monitoring method. Results Histopathology results indicated a significantly lower extent of esophageal tissue damage in the FLASH group compared to the CONV group (p < 0.05). Label-free quantitative proteomic analysis revealed that the sparing effect observed in the FLASH group may be attributed to a reduction in radiation-induced protein damage associated with mitochondrial functions, including proteins involved in the tricarboxylic acid cycle and oxidative phosphorylation, as well as a decrease in acute inflammatory responses. Conclusions Compared with CONV irradiation, a sparing effect on esophageal tissue can be observed after FLASH irradiation. This sparing effect is associated with alleviated mitochondria damage and acute inflammation.